AB0482 Elevation of serum proprotein convertase subtilisin/kexin type 9 (PCSK9) concentrations and its correlation with C-reactive protein, but not atherogenic lipids in patients with systemic lupus erythematosus. (15th June 2017) - Fang, C; Huang, L; Luo, T; Chen, X; Lin, L
Abstract : Background: Patients with systemic lupus erythematosus (SLE) have a tendency of accelerated atherosclerosis with controversial benefits from statin. This phenomenon can only partly be explained by traditional risk factors for cardiovascular disease. Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a serine protease associated with cardiovascular risk that not only regulates cholesterol metabolism, but acts as a critical regulator of inflammatory reaction. PCSK9 inhibitors were also highly promising drugs bringing added cardiovascular benefit when administered with statin [1] [2]. Objectives: The present study firstly aimed to compare serum PCSK9 levels in SLE patients and healthy controls. The association between PCSK9 concentrations with atherogenic lipids and C-reactive protein (CRP) in SLE patients was also analyzed. Methods: 77 individuals encompassed; 47 patients with SLE and 30 age- and sex-matched controls. Serum PCSK9, lipoproteins concentrations and CRP levels were assessed in patients and controls. Individuals with history of smoking, diabetes, infection, tumor and statin use were excluded. Results: Serum PCSK9 levels were significantly elevated in patients with SLE, compared with healthy controls (p=0.034). PCSK9 positively correlated with serum levels of CRP (rs =0.351, p=0.016); The tendency seemed more significant in female patients (rs =0.487, p=0.001); No correlation with statistical significance between PCSK9 levels with disease activity (SLEDAI) or serum lipids parameter was found (p>0.05, all) (Table 1 ). Conclusions: Elevation of PCSK9 was observed in patients with SLE and correlated with CRP but not atherogenic lipids, particularly in female patients. The result was indicative of pathogenic role of PCSK9 in the low-grade inflammation which promotes the atherogenic process in SLE patients. References: Giugliano RP, Sabatine MS. Are PCSK9 Inhibitors the Next Breakthrough in the Cardiovascular Field?. J Am Coll Cardiol. 2015 Jun 23;65(24):2638–51. Walley KR, Thain KR, Russell JA, et al. PCSK9 is a critical regulator of the innate immune response and septic shock outcome.Sci Transl Med. 2014 Oct 15;6(258):258ra143. Acknowledgements: The authors thank Qiulan Li for the excellent technical assistance. Disclosure of Interest: None declared